2021
DOI: 10.47153/sss13.2542021
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Motivation in Learning English Through English Learning Videos Making

Abstract: Video is a common media to use in teaching English in the past few years. English learning video can be an external factor that influence students’ motivation in studying English. English learning video that was designed by involving students as the actors predicted to have some common sense of belonging. Related to the purpose of the research, the result showed the students were motivated even more by learning English in a class using the video they are involved. Focusing on research methodology, descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Perseverance in learning refers to persistence at a learning task, which is evidenced to can be promoted by task enjoyment (Leonard and Weitz, 1971). The benefits of video creation have since been replicated in other studies (Huang, 2015;Sari et al, 2020;Erlangga, 2021;Jung, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perseverance in learning refers to persistence at a learning task, which is evidenced to can be promoted by task enjoyment (Leonard and Weitz, 1971). The benefits of video creation have since been replicated in other studies (Huang, 2015;Sari et al, 2020;Erlangga, 2021;Jung, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on learning strategies has shown that creating a video can be an effective strategy for learning ( Hoogerheide et al, 2019 ; Erlangga, 2021 ; Zainuddin and Che’ Lah, 2022 ). For example, the study by Zainuddin and Che’ Lah (2022) tested the effects of video creation in English classrooms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When they learn English through song and video, young students are more motivated and have a positive attitude toward the language. (Erlangga 2021;Han et al 2010). Songs, which contain both music and lyrics, are regarded as particularly effective language-learning tools for teaching young students to listen.…”
Section: Young Learners Are Enthusiastic and Positive About Learningmentioning
confidence: 99%